Timber drying by using solar kiln drying / Siti Sarah Alias - Alias, Siti Sarah (2006)
This project is about drying timber by using solar kiln drying which include the method of how its work, concept, equipment and tools, design and the benefits of using solar kiln drying to drying the product even wood or food. Solar kiln drying is famous their using in Western country, Uganda, Morocco, and our neighbour country Thailand. From this project I got drying by using solar kiln is more efficiency and save cost and energy.